Inequality in School Readiness and Autism among 6-Year-Old Children across Iranian Provinces: National Health Assessment Survey Results - Amiri, Masoud (Tehran University of Medical Sciences, 2013)
OBJECTIVE: To assess the national inequality of school readiness and autism among 6-year-old Iranian children before school entry using a national health assessment survey. METHODS: In a cross-sectional nationwide survey, all Iranian children entering public and private elementary schools were asked to participate in a mandatory national screening program in Iran in 2009 in two levels of screening and diagnostic levels. FINDINGS: The study population consisted of 955388 children (48.5% girls and 76.1% urban residents). Of the whole children, 3.1% of the 6-year-old children had impaired vision. In addition, 1.2, 1.8, 1.4, 7.6, 0.08, 10, 10.9, 56.7, 0.7, 0.8 and 0.6 percent had color blindness, hearing impaired, speech disorder, school readiness, autism, height to age retardation, body mass index extremes, decayed teeth, disease with special needs, spinal disorders, and hypertension, respectively. The distribution of these disorders was unequally distributed across provinces. CONCLUSION: Our results confirmed that there is an inequality in distribution of school readiness and autism in 6-year-old children across Iranian provinces. The observed burden of these distributions among young children needs a comprehensive national policy with evidence-based province programs to identify the reason for different inequality among provinces.